Gelation or molecular recognition; is the bis-(α,β-dihydroxy ester)s motif an omnigelator? - Griffiths, Peter C.; Knight, David W.; Morgan, Ian R.; Ford, Amy; Brown, James; Davies, Ben; Heenan, Richard K.; King, Stephen M.; Dalgliesh, Robert M.; Tomkinson, John; Prescott, Stuart; Schweins, Ralf; et al. (Beilstein Journal of Organic Chemistry, 2010)
Understanding the gelation of liquids by low molecular weight solutes at low concentrations gives an insight into many molecular recognition phenomena and also offers a simple route to modifying the physical properties of the liquid. Bis-(α,β-dihydroxy ester)s are shown here to gel thermoreversibly a wide range of solvents, raising interesting questions as to the mechanism of gelation. At gelator concentrations of 5–50 mg ml−1, gels were successfully formed in acetone, ethanol/water mixtures, toluene, cyclohexane and chloroform (the latter, albeit at a higher gelator concentration). A range of neutron techniques – in particular small-angle neutron scattering (SANS) – have been employed to probe the structure of a selection of these gels. The universality of gelation in a range of solvent types suggests the gelation mechanism is a feature of the bis-(α,β-dihydroxy ester) motif, with SANS demonstrating the presence of regular structures in the 30–40 Å range. A correlation between the apparent rodlike character of the structures formed and the polarity of the solvent is evident. Preliminary spin-echo neutron scattering studies (SESANS) indicated the absence of any larger scale structures. Inelastic neutron spectroscopy (INS) studies demonstrated that the solvent is largely unaffected by gelation, but does reveal insights into the thermal history of the samples. Further neutron studies of this kind (particularly SESANS and INS) are warranted, and it is hoped that this work will stimulate others to pursue this line of research.
Keywords: gelation; inelastic neutron spectroscopy; low molar mass organogelator; neutron scattering; neutron spin-echo scattering; self-assembly